1992
DOI: 10.1002/jcu.1870200906
|View full text |Cite
|
Sign up to set email alerts
|

A prospective comparative study of transvaginal ultrasonography and digital examination for cervical assessment in the third trimester of pregnancy

Abstract: Digital examination of the cervix has traditionally been the "gold standard" for cervical assessment. However, it can be subject to inter- as well as intra-observer variation. The usefulness of transvaginal ultrasonography for cervical assessment is examined in this study. Although differences between measurements of transvaginal ultrasonography and digital examinations were observed, transvaginal ultrasonography appears to be a potentially useful and reproducible technique for assessing cervical changes in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
4

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
3
0
4
Order By: Relevance
“…It has been suggested that preterm labor can be predicted in twin pregnancies by serial digital examination (3). Transvaginal ultrasound correlates well with digital findings and has the advantage over digital examination, because it avoids the theoretical risk of prostaglandin release, allows for the whole length of the cervix to be measured and minimizes inter-observer error (4). Although transabdominal ultrasound can be used to visualize the cervix, transvaginal ultrasound is more accurate, reproducible and is better at predicting preterm delivery in singletons (5).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that preterm labor can be predicted in twin pregnancies by serial digital examination (3). Transvaginal ultrasound correlates well with digital findings and has the advantage over digital examination, because it avoids the theoretical risk of prostaglandin release, allows for the whole length of the cervix to be measured and minimizes inter-observer error (4). Although transabdominal ultrasound can be used to visualize the cervix, transvaginal ultrasound is more accurate, reproducible and is better at predicting preterm delivery in singletons (5).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have shown that ultrasonographic cervical assessment is more accurate than digital examination for identifying cervical changes (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…However, the Bishop score is a subjective method of assessing the cervix and it has been reported to be of limited value in women with a low score, as a predictor of successful induction [8,9] . Transvaginal sonographic measurement of the cervical length has been reported recently as a method which can provide a more sensitive prediction of successful labor induction [10,11] . Although transvaginal ultrasonographic cervical measurement is easily reproducible and quantitative, several studies have demonstrated confl icting results [12][13][14][15] .…”
mentioning
confidence: 99%